2008
DOI: 10.1007/s10729-008-9068-5
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the effectiveness of a pediatric vaccine formulary while prohibiting extraimmunization

Abstract: The growing-complexity of the United States Recommended Childhood Immunization Schedule has resulted in as many as five required injections during a single well-baby office visit. To reduce this number, vaccine manufacturers have developed combination vaccines that immunize against several diseases in a single injection. At the same time, a growing number of parents are challenging the safety and effectiveness of vaccinating children. They are also particularly concerned about the use of combination vaccines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Those studies have found: that commonly reported errors involved wrong vaccine or improper dosing; adverse health outcomes were uncommon [3]; that about10-35% of young children had at least 1 invalid dose administered [4,5]; and that a voluntary, team approach was effective in improving error reporting [6]. Several other studies have reported on specific vaccination errors including: extra immunization [7,8]; improper spacing of vaccine doses [9]; improper route [10,11]; expired vaccine [12]; improper storage [13] wrong drug administered [14]; and contraindication errors [15]. Other publications have highlighted possible contributors to errors, such as names and abbreviations which can soundalike and packaging that can look alike [16,17].…”
mentioning
confidence: 99%
“…Those studies have found: that commonly reported errors involved wrong vaccine or improper dosing; adverse health outcomes were uncommon [3]; that about10-35% of young children had at least 1 invalid dose administered [4,5]; and that a voluntary, team approach was effective in improving error reporting [6]. Several other studies have reported on specific vaccination errors including: extra immunization [7,8]; improper spacing of vaccine doses [9]; improper route [10,11]; expired vaccine [12]; improper storage [13] wrong drug administered [14]; and contraindication errors [15]. Other publications have highlighted possible contributors to errors, such as names and abbreviations which can soundalike and packaging that can look alike [16,17].…”
mentioning
confidence: 99%
“…In the area of asset allocation problems, the primary application of such research has been to vaccine formulary design optimization. Hall et al (2008a) formulate an integer programming model that solves for the maximum number of vaccines that can be administered without any extraimmunization for pediatric immunization. An exact dynamic programming algorithm and a randomized heuristic for the integer programming model is also formulated and the heuristic is shown to be a harmonic approximation algorithm.…”
Section: Other Research Resultsmentioning
confidence: 99%